Effect of intellectual capital disclosure on cost of equity capital: a study on Indian companies - Amitava Mondal; Chiranjit Ghosh (Asian Journal of Accounting Research, 2020)
The impact of the intellectual capital disclosure (ICD) on the cost of equity capital (COEC) is not well established in the aspect of the Indian scenario. So the objective of this paper is to examine not only the overall effect of ICD but also the individual effect of human capital disclosure (HCD), relational capital disclosure (RCD) and structural capital disclosure (SCD) on COEC.This research work is conducted by regressing COEC, firm size, leverage, industry type and disclosure index. The disclosure index is prepared based on content analysis of disclosure made in the annual reports of a sample of 50 companies listed in the Nifty 50 index for the year 2018–2019. But in this paper 20 companies are eliminated due to their negative COEC and rest 30 companies are used as the sample companies for this study.The outcome of this study indicates a negative association between the disclosure of intellectual capital (IC) as a whole and the COEC. But a negative association only for two components (human capital and structural capital) with the COEC is found only when the association of COEC with the categories of ICD is considered.This is the first study that examines the nexus between the level of ICD and its impact on the COEC in India context.